Nomenclatural type designation of four Linnaean names in Iris sensu lato (Iridaceae) - Altinordu, Fahim; Crespo, Manuel B. (Phytotaxa, 2016)
The typification of four Linnaean names, Iris susiana, I. sibirica, I. persica and I. spuria, is discussed. Lectotypes are designated using specimens from the Linnaean and van Royen herbaria. Furthermore, an epitype for I. spuria is also selected, since the lectotype designated here is heavily damaged by insects. Synonyms for all concerned names in recent alternative generic treatments are also included in brackets.